Pengaruh Digitalisasi Pajak (Electronic System) Terhadap Peningkatan Kepatuhan Wajib Pajak - Yosefin; Mutiara Anjelika (PT FORMOSA CENDEKIA GLOBAL, 2022)
The study was conducted to determine the comparison between before and after the use of e-registration, e-SPT, e-filing on the performance of KPP Pratama Jakarta Gambir Tiga from the period 2016-2019. From the analysis carried out using a comparison of registered taxpayers, active taxpayers, and taxpayers who report their tax returns electronically (e-SPT), in the end the number of residents in the work area who have the potential to become taxpayers. By using e-Filling, Taxpayers can submit their notification letters online through application service providers to the Directorate General of Taxes. Taxpayers get many benefits with the implementation of e-Filing, namely tax data processing becomes faster, more precise and accurate, can avoid paper wastage and is more efficient. In addition, taxpayers can submit their tax returns anytime and anywhere. The research method used is descriptive qualitative method with interview results comparing before and after the use of e-Registration, e-SPT, e-Filing at KPP Pratama Jakarta Gambir Tiga, and plus primary data, the data is taken by downloading directly on the Information System application. Directorate General of Taxes (SI DGT) and the data are time-series. Then the data that has been collected is tabulated and compared for analysis. The conclusion obtained from this study is that for 2 years the implementation of e-Registration, e-SPT, e-Filing continues to increase, so that total tax revenue also increases a lot.